Hubungan kadar asam lemak dengan fungsi hati pada remaja obes - Pasaribu, Eca D.Y.; Warouw, Sarah M.; Rampengan, Novie H. (Universitas Sam Ratulangi, 2016)
Abstract: Obesity has reached epidemic proportion globally. Obesity is the risk factors to various diseases and early death. Being obese in adolescents is highly risky to become obese in adults and potentially have metabolic diseases and degenerative diseases later. Early detection of the changes in liver function is crucial in obese adolescents. The prevelation of non-alcoholic fatty liver disease increase simultaneously as the increase of the number of obesity in children and adolescents. This study was aimed to obtain the correlation of fatty acid level and liver function in obese adolescents. This was an observational study with a cross sectional design. Population was male and female obese students aged 13-15 years in Tomohon. Anthopometry value, trygliceride level, and the serum marker of liver function (AST and ALT) were examined. The respondents fasted for 10 to 12 hours before the blood examination. There were 39 obese adolescents as samples. The result of the Pearson Correlation test showed a positive correlation between trygliceride level and AST level but not statistically significant (r=0.048, p=0.772) and a positive correlation between trygliceride level and ALT level but not statistically significant (r=0.068, p=0.679). Conclusion: There was a a positive correlation between the fatty acid level and the liver function in obese adolescents,however, it was not statistically significant.Keywords: obesity, adolescents, trygliceride, AST, ALTÂ Abstract: Obesitas telah mencapai proporsi epidemik global. Obesitas merupakan predisposisi terhadap penyakit dan kematian dini akibat berbagai penyakit. Obesitas pada masa anak berisiko tinggi menjadi obesitas di masa dewasa dan berpotensi mengalami berbagai penyakit metabolik dan penyakit degeneratif di kemudian hari. Deteksi dini adanya perubahan fungsi hati penting dilakukan pada anak obes. Prevalensi penyakit perlemakan hati non alkoholik meningkat bersamaan dengan meningkatnya obesitas pada anak dan remaja. Penelitian ini bertujuan untuk mengetahui hubungan kadar asam lemak dan fungsi hati pada remaja obes. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Populasi ialah siswa-siswi remaja obes berusia 13-15 tahun di Kota Tomohon. Dilakukan pengukuran antopometri, pemeriksaan trigliserida, dan serum penanda fungsi hati (AST dan ALT). Sampel penelitian berjumlah 39 remaja obes. Hasil uji korelasi Pearson menunjukkan hubungan positif antara kadar trigliserida dengan kadar AST namun tidak bermakna secara statistik (r=0,048, p=0,772) dan terdapat pula hubungan positif antara kadar trigliserida dengan ALT namun tidak bermakna secara statistik (r=0,068, p=0,679). Simpulan: Terdapat hubungan positif antara kadar asam lemak dengan fungsi hati pada remaja obes namun tidak bermakna secara statistik. Kata kunci: obesitas, remaja, trigliserida, AST, ALT